Framing archaeology in the Near East the application of social theory to fieldwork - Milevski, Ianir 1955-; Levy, Thomas Evan 1953- (Sheffield, UK Bristol, CT equinox, 2016)
"This volume presents a series of studies by scholars working in Middle Eastern archaeology who actively apply social theory to interpret their fieldwork. It aims to highlight the value of using social theory in the interpretation of field work in a region where, traditionally, such approaches have not played a major role. There are a number of factors that account for why social theory is often under-exploited by archaeologists in this part of the world. In many countries, where large numbers of the foreign archaeologists are involved, a division between those doing fieldwork and those undertaking archaeological interpretation can easily arise. Or, the lack of interest in social theory may stem from a legacy of positivism that overrides other approaches. There is also the fact that archaeology and anthropology often belong to separate academic departments and are considered two separate disciplines disconnected from each other. In some cases the centrality of historical paradigms has precluded the use of social theory. There are also divisions between universities and other research institutions, such as departments of antiquities, which is not conductive to interdisciplinary cooperation. This factor is especially debilitating in contexts of rapid destruction of sites and the exponential growth of salvage excavations and emergency surveys. The papers integrate a wide range of perspectives including 'New' or 'Processual' archaeology, Marxist, 'Post-Processual', evolutionist, cognitive, symbolic, and Cyber- archaeologies and touch on many topics including 3D representation, GIS, mapping and social theory, semiotics and linguistics, gender and bioarchaeology, social and technical identities, and modern historical modellingy and social practices"--Provided by publisher
Introduction: Social theory and archaeology / Ianir Milevski and Thomas E. LevySpacetime mapping the ancient Near East : scalability and seamlessness in theory and practice of spatial archaeology / Michael Harrower -- Gender and the archaeology of the ancient Near East : femininities and masculinities / Joanna Mardas -- Perspectives on sex and gender questions through burial practices in southern Central Asia during the Bronze Age / Elise Luneau -- Semiotics in action : Neolithic imagery on the move / Patrycja Filipowicz -- The role of communication in late 3rd millennium BC Mesopotamian society supported by cross-disciplinary interpretative tools / Alessandro Di Ludovico -- Social theories, technical identities, cultural boundaries : a perspective on the "colonial situation" in late Chalcolithic 3-5 northern Mesopotamia / Johnny Samuele Baldi -- New social perspectives on intermediate Bronze Age burial practices at Jericho / Aaron Greener -- The kingdom of Edom? : a critical reappraisal of the Edomite state model / Juan Manuel Tebes -- Biblical archaeology, processualism, post-processualism and beyond / Ianir Milevski and Bernardo Gandulla.
Includes bibliographical references and index
Auch als Online-Ausgabe vorhanden
Keywords: Social archaeology -- Middle East; Archaeology -- Fieldwork -- Middle East; Excavations (archaeology) -- Middle East; Archaeology -- Philosophy; Social Sciences -- Philosophy; Anthropology -- Philosophy; Social archaeology -- Middle East; Archaeology -- Fieldwork -- Middle East; Excavations (archaeology) -- Middle East; Archaeology -- Philosophy; Social Sciences -- Philosophy; Anthropology -- Philosophy; Middle East -- Antiquities; Middle East -- Antiquities; Aufsatzsammlung; Konferenzschrift -- 2012 -- Warschau